Long-term outcomes of empirical extra-pulmonary vein linear ablation in patients with persistent atrial fibrillation. (24th May 2021) - Hwang, T; Kim, M; Yu, H; Kim, T; Uhm, J; Joung, B; Lee, M; Pak, H
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): This work was supported by grants [HI18C0070] and [HI19C0114] from the Korea Health 21 R&D Project, Ministry of Health and Welfare, and a grant [NRF-2020R1A2B01001695] from the Basic Science Research Program run by the National Research Foundation of Korea (NRF). Background: Although extra-pulmonary vein (PV) left atrial (LA) linear ablation has been performed during catheter ablation (CA) of persistent atrial fibrillation (PeAF), the long-term efficacy and safety of this procedure have not yet been verified. Purpose: We investigated whether an anterior line (AL) and posterior box ablation (POBA) in addition to circumferential PV isolation (CPVI) improves the rhythm without worsening the LA function in PeAF patients. Methods: We retrospectively compared the additional AL + POBA and CPVI alone groups in 604 patients with PeAF who underwent regular rhythm follow-ups (16.9%; males 79.3%, 58.5 ± 10.7 years of age) after propensity score matching. The primary endpoint was AF recurrence after single procedures and secondary endpoints were the cardioversion rate, response to anti arrhythmic drugs, LA changes, and re-conduction rates of the de-novo ablation lesion set. Results: After a mean follow-up of 45.2 ± 33.6 months, the clinical recurrence rate did not significantly differ between the two groups (log-rank p = 0.554) despite longer procedure times in the AL + POBA group (p < 0.001). Atrial tachycardia recurrences (p = 0.001) and the cardioversion rates after ablation (p < 0.001) were higher in the AL + POBA group than CPVI group. AL + POBA was associated with better rhythm outcomes in patients with large anterior LA volume indices (p for interaction 0.037) and low mean LAA(left atrial appendage) voltages (p for interaction 0.019). In repeat procedures, the LA pulse pressure elevation was significant after the AL + POBA. Conclusion: In patients with PeAF, an AL + POBA in addition to the CPVI did not improve the rhythm outcomes nor influence the long-term safety, and lead to more extended procedures.